Oxygen-containing compound adsorbent and preparation method thereof

By using the first metal modified molecular sieve and the second metal modified activated alumina as adsorbent, the problems of small adsorption capacity and low selectivity in the prior art are solved, and the effect of efficiently removing oxygen-containing compounds in Fischer-Tropsch synthetic oil is achieved.

CN119608105APending Publication Date: 2025-03-14CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411743191.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the adsorbents that remove oxygen-containing compounds from Fischer-Tropsch synthetic oil have problems with small adsorption capacity and low adsorption selectivity.

Method used

The first metal modified modified molecular sieve and the second metal modified modified activated alumina are used as active components, and the adsorption center is increased and the surface chemical properties are improved through the modified molecular sieve, and the effective contact area is increased in combination with the activated alumina, and the adsorption performance is improved.

Benefits of technology

The selectivity and adsorption capacity of oxygen-containing compounds in C4 to C12 Fischer Tropsch synthetic oil can be significantly improved, and the content of oxygen-containing compounds in Fischer Tropsch synthetic oil can be reduced to less than 1 ppm, providing raw materials suitable for downstream polyolefin product production processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162951030000111
    Figure BDA0005162951030000111
  • Figure BDA0005162951030000121
    Figure BDA0005162951030000121
Patent Text Reader

Abstract

The invention provides an oxygen-containing compound adsorbent and a preparation method thereof. The oxygen-containing compound adsorbent comprises an active component; the active component comprises a first metal-modified modified molecular sieve and a binder attached to the surface of the modified molecular sieve; the binder is modified activated aluminum oxide modified by second metal; metal elements related to the first metal modification and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements. The oxygen-containing compound adsorbent has high selectivity and high adsorption capacity on oxygen-containing compounds in C4-C12 Fischer-Tropsch synthetic oil, the content of the oxygen-containing compounds in the Fischer-Tropsch synthetic oil raw material can be reduced to 1 ppm or below, and meanwhile, a raw material is provided for a downstream polyolefin product production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of oxygen-containing compound adsorbents, and in particular to an oxygen-containing compound adsorbent and a preparation method thereof. Background Art

[0002] Fischer-Tropsch washed naphtha is characterized by a high α-olefin content. The olefin products obtained through separation and purification can be used to produce downstream high-end polyolefin products such as POP and POE. However, Fischer-Tropsch washed naphtha also contains a certain amount of oxygenated compounds, such as alcohols, aldehydes, ketones, acids, and esters, and the types are complex. The alkane and olefin products produced after separation still contain a small amount of oxygenated compounds after crude desulfurization, and therefore cannot meet the requirements of polymerization-grade monomers.

[0003] Currently, methods for removing oxygenates from washed naphtha from Fischer-Tropsch synthesis oil primarily include hydrogenation, extraction, distillation, pervaporation, and adsorption. However, extraction and distillation methods suffer from incomplete oxide removal and inability to achieve the required depth of purification. Adsorption can remove trace oxides from Fischer-Tropsch synthesis oil, but one of the key challenges of this technology is the difficulty in selecting and designing the adsorbent material. Currently, most adsorption processes for removing oxygenates from Fischer-Tropsch synthesis oil use fixed-bed adsorption separation processes, primarily using molecular sieves as adsorbents. However, the hydrocarbon products produced by Fischer-Tropsch synthesis have varying carbon number distributions, and the various oxygenates present in each carbon number product are diverse. Consequently, these adsorbents suffer from limited adsorption capacity, insufficient oxide removal depth, and low selectivity for the types of oxides removed. Modifying the adsorption performance by subjecting the formed adsorbent to solution ion exchange, which modifies the surface properties of the adsorbent, can affect the strength of the finished adsorbent. Summary of the Invention

[0004] The main purpose of the present invention is to provide an oxygen-containing compound adsorbent and a preparation method thereof, so as to solve the problems of small adsorption capacity and low adsorption selectivity of adsorbents for removing oxygen-containing compounds from Fischer-Tropsch synthetic oil in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided an oxygen-containing compound adsorbent, which includes an active component; the active component includes a modified molecular sieve modified with a first metal and a binder attached to the surface of the modified molecular sieve; the binder is a modified activated alumina modified with a second metal; the metal elements involved in the first metal modification and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

[0006] Furthermore, the mass content of the first metal element in the modified molecular sieve is 0.05-10%; and / or, the mass content of the second metal element in the modified activated alumina is 0.01-5%; and / or, based on the total mass of the modified molecular sieve and the binder as 100%, the mass of the modified molecular sieve accounts for 45-95%, preferably 50-80%; and / or, the raw powder of the modified molecular sieve is selected from any one or more of FAU-type framework structure molecular sieve, LTA-type framework structure molecular sieve, MFI-type framework structure molecular sieve and CHA-type framework structure molecular sieve.

[0007] Furthermore, the transition metal element is selected from any one or more of Ni, Co, Fe, Mn, Cu, Zn, Ag, Cr, Zr and Ti; preferably, the alkaline earth metal is selected from any one or more of Ca, Ba, Sr and Mg; preferably, the rare earth metal is selected from any one or more of Ce, La, Y and Nd.

[0008] Furthermore, the oxygen-containing compound adsorbent also includes an additive, and the mass content of the additive is 1 to 20% based on the total mass of the modified molecular sieve and the binder as 100%, and / or the additive is selected from any one or more of methyl cellulose, sesbania powder, guar gum, carboxymethyl cellulose, maltodextrin, starch, polyethylene glycol, glycerol, sodium carboxymethyl cellulose and polyvinyl alcohol.

[0009] According to another aspect of the present invention, a method for preparing the above-mentioned oxygen-containing compound adsorbent is provided, which comprises: step S1, pre-treating and first metal ion-exchanging the molecular sieve in sequence to obtain a modified molecular sieve; step S2, performing a second metal modification on the activated alumina to obtain a binder; and step S3, mixing, molding, first drying and roasting the raw materials including the modified molecular sieve and the binder in sequence to obtain the oxygen-containing compound adsorbent; wherein the metal elements involved in the first metal ion exchange and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

[0010] Furthermore, in the above step S1, the molecular sieve is pretreated with a NaAlO2 solution to obtain a pretreated molecular sieve, and the pretreated molecular sieve is sequentially subjected to a second drying and crushing to obtain a first molecular sieve; the molar concentration of the NaAlO2 solution is 0.01 to 0.1 mol / L, the silicon-aluminum ratio of the pretreated molecular sieve is 2 to 50, and the size of the first molecular sieve is 100 to 300 mesh; and / or the pretreatment time is 1 to 24 h, and / or the second drying temperature is 60 to 150°C, and / or the second drying time is 12 to 48 h.

[0011] Furthermore, in the above step S1, the first metal salt solution is used to perform a first metal ion exchange on the first molecular sieve to obtain a second molecular sieve; the ratio of the mass of the first molecular sieve to the volume of the first metal salt solution is 1:5~60kg / L, and / or the temperature of the first metal ion exchange is 40~100℃; and / or, the second molecular sieve is washed, dried and crushed in sequence to obtain a modified molecular sieve, the size of the modified molecular sieve is 100~300 mesh, preferably washed with deionized water, and / or the temperature of the third drying is 60~120℃.

[0012] Furthermore, in the above step S2, the activated alumina is modified with a second metal using a second metal salt solution and then dried to obtain a binder; the ratio of the mass of the activated alumina to the volume of the second metal salt solution is 1:1~5kg / L, and / or the drying temperature is 100~150℃, and / or the drying time is 10~48h, and / or the size of the binder is 100~300 mesh.

[0013] Furthermore, the molar concentrations of the first metal salt solution and the second metal salt solution are each independently 0.005 to 0.5 mol / L, and / or the first metal salt solution and the second metal salt solution are each independently selected from any one or more of metal nitrate solution, metal carbonate solution and metal acetate solution.

[0014] Furthermore, the raw materials also include auxiliary agents, and / or the mixed mixture is molded using an acid solution to obtain molded particles, the acid solution is a nitric acid solution and / or a citric acid solution, and the size of the molded particles is 1.5 to 3.5 mm; and / or the first drying temperature is 60 to 150° C., and the roasting temperature is 450 to 600° C.

[0015] Applying the technical solution of the present invention, the present application provides an adsorbent suitable for fixed bed adsorption removal of oxygen-containing compounds in Fischer-Tropsch synthetic oil. The oxygen-containing compound adsorbent uses the modified molecular sieve modified with the first metal of the above type as an active component, which can increase the adsorption center in the modified molecular sieve framework and improve the chemical properties of its surface, thereby further regulating the adsorption performance of the modified molecular sieve. Selecting the mesoporous material activated alumina modified with the second metal of the above type as a molding binder can increase the effective contact area between the adsorbent and the oxygen-containing compound, thereby making it easy for the oxygen-containing compound to diffuse in the pores, thereby improving the selectivity and adsorption capacity of the oxygen-containing compound adsorbent for oxygen-containing compounds. In summary, the oxygen-containing compound adsorbent of the present invention has a good adsorption capacity for C4~C 12The oxygen-containing compounds in Fischer-Tropsch oil (including alcohol compounds, acid compounds, aldehyde compounds, ketone compounds, ester compounds and ether compounds) have high selectivity and high adsorption capacity, which can reduce the content of oxygen-containing compounds in Fischer-Tropsch oil raw materials to below 1 ppm, and at the same time provide raw materials for downstream polyolefin product production processes. DETAILED DESCRIPTION

[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the embodiments.

[0017] As analyzed in the background technology of this application, the adsorbents for removing oxygenated compounds from Fischer-Tropsch synthetic oil in the prior art have problems such as small adsorption capacity and low adsorption selectivity. In order to solve the above problems, this application provides an oxygenated compound adsorbent and a preparation method thereof.

[0018] In a typical embodiment of the present application, an oxygen-containing compound adsorbent is provided, which includes an active component; the active component includes a modified molecular sieve modified with a first metal and a binder attached to the surface of the modified molecular sieve; the binder is a modified activated alumina modified with a second metal; the metal elements involved in the first metal modification and the second metal modification are each independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

[0019] The present application provides an adsorbent suitable for fixed bed adsorption removal of oxygen-containing compounds in Fischer-Tropsch synthetic oil. The oxygen-containing compound adsorbent uses the modified molecular sieve modified with the first metal of the above type as an active component, which can increase the adsorption center in the modified molecular sieve framework and improve the chemical properties of its surface, thereby further regulating the adsorption performance of the modified molecular sieve. The use of the mesoporous material activated alumina modified with the second metal of the above type as a molding binder can increase the effective contact area between the adsorbent and the oxygen-containing compound, thereby making it easy for the oxygen-containing compound to diffuse in the pores, thereby improving the selectivity and adsorption capacity of the oxygen-containing compound adsorbent for oxygen-containing compounds. In summary, the oxygen-containing compound adsorbent of the present invention has a good adsorption capacity for C4~C 12 The oxygen-containing compounds in Fischer-Tropsch oil (including alcohol compounds, acid compounds, aldehyde compounds, ketone compounds, ester compounds and ether compounds) have high selectivity and high adsorption capacity, which can reduce the content of oxygen-containing compounds in Fischer-Tropsch oil raw materials to below 1 ppm, and at the same time provide raw materials for downstream polyolefin product production processes.

[0020] In one embodiment of the present application, the mass content of the first metal element in the modified molecular sieve is 0.05-10%; and / or, the mass content of the second metal element in the modified activated alumina is 0.01-5%; and / or, based on the total mass of the modified molecular sieve and the binder as 100%, the mass proportion of the modified molecular sieve is 45-95%, preferably 50-80%; and / or, the raw powder of the modified molecular sieve is selected from any one or more of FAU-type framework structure molecular sieve, LTA-type framework structure molecular sieve, MFI-type framework structure molecular sieve and CHA-type framework structure molecular sieve.

[0021] Preferably, the mass content of the first metal element in the modified molecular sieve and the type of raw powder of the modified molecular sieve are within the above ranges, which helps to further improve the surface chemical properties of the modified molecular sieve and regulate the pores and micropores of the molecular sieve, thereby helping to separate the oxygen-containing compounds in the Fischer-Tropsch synthetic oil, and thus improve the adsorption capacity of the oxygen-containing compound adsorbent and the selectivity for oxygen-containing compounds. Preferably, the mass content of the second metal element in the modified activated alumina is within the above range, which helps to further increase the effective contact area with the oxygen-containing compounds, thereby further improving the selectivity and adsorption capacity of the adsorbent for oxygen-containing compounds. Preferably, the mass ratio of the modified molecular sieve and the binder is within the above range, which helps to further improve the adsorption capacity and selectivity of the oxygen-containing compound adsorbent for oxygen-containing compounds.

[0022] In one embodiment of the present application, the transition metal element is selected from any one or more of Ni, Co, Fe, Mn, Cu, Zn, Ag, Cr, Zr and Ti; preferably, the alkaline earth metal is selected from any one or more of Ca, Ba, Sr and Mg; preferably, the rare earth metal is selected from any one or more of Ce, La, Y and Nd.

[0023] It is preferred that the types of the above-mentioned metal elements are within the above-mentioned range, which helps to further improve the modification effect of the molecular sieve and activated alumina, thereby enhancing the selectivity of the oxygen-containing compound adsorbent for oxygen-containing compounds and improving its adsorption stability, so that it can maintain good adsorption efficiency under high temperature and high humidity conditions.

[0024] In one embodiment of the present application, the oxygen-containing compound adsorbent further includes an additive, and the mass content of the additive is 1 to 20% based on the total mass of the modified molecular sieve and the binder as 100%, and / or the additive is selected from any one or more of methyl cellulose, sesbania powder, guar gum, carboxymethyl cellulose, maltodextrin, starch, polyethylene glycol, glycerol, sodium carboxymethyl cellulose and polyvinyl alcohol.

[0025] It is preferred to control the type and mass content of the auxiliary agent within the above range, which helps to improve the molding performance and strength of the oxygen-containing compound adsorbent, thereby minimizing the problem of reducing its adsorption efficiency due to wear.

[0026] In another typical embodiment of the present application, a method for preparing the above-mentioned oxygen-containing compound adsorbent is provided, which comprises: step S1, pre-treating and exchanging the molecular sieve with a first metal ion in sequence to obtain a modified molecular sieve; step S2, performing a second metal modification on the activated alumina to obtain a binder; and step S3, mixing, molding, first drying and roasting the raw materials including the modified molecular sieve and the binder in sequence to obtain the oxygen-containing compound adsorbent; wherein the metal elements involved in the first metal ion exchange and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

[0027] The present application modifies the powder skeleton and non-skeleton elements of the molecular sieve through step S1, and its silicon-aluminum ratio can be reduced through pretreatment. The higher aluminum content in the molecular sieve with a low silicon-aluminum ratio makes it have more balanced cations and a stronger electrostatic field and more adsorption centers in its framework. The chemical properties of the molecular sieve surface can be improved by the first metal ion exchange, thereby improving the selectivity of the molded adsorbent for oxygen-containing compounds in Fischer-Tropsch oil. Modifying the activated alumina with a second metal and using it as a molding binder can increase the effective contact area with the oxygen-containing compound, thereby making it easy for the oxygen-containing compound to diffuse in the pores, and the adsorption capacity of the activated alumina itself can be further improved after the second metal modification, so that the oxygen-containing compound adsorbent has a higher adsorption capacity, while reducing the amount of molecular sieve added to the molded adsorbent, thereby reducing the preparation cost. The oxygen-containing compound adsorbent obtained by the above preparation method has a high selectivity for C4~C 12 The oxygen-containing compounds in Fischer-Tropsch oil (including alcohol compounds, acid compounds, aldehyde compounds, ketone compounds, ester compounds and ether compounds) have high selectivity and high adsorption capacity, which can reduce the content of oxygen-containing compounds in Fischer-Tropsch oil raw materials to below 1 ppm, and at the same time provide raw materials for downstream polyolefin product production processes.

[0028] In one embodiment of the present application, in the above step S1, the molecular sieve is pretreated with a NaAlO2 solution to obtain a pretreated molecular sieve, and the pretreated molecular sieve is sequentially subjected to a second drying and crushing to obtain a first molecular sieve; the molar concentration of the NaAlO2 solution is 0.01 to 0.1 mol / L, the silicon-aluminum ratio of the pretreated molecular sieve is 2 to 50, and the size of the first molecular sieve is 100 to 300 mesh; and / or the pretreatment time is 1 to 24 h, and / or the second drying temperature is 60 to 150°C, and / or the second drying time is 12 to 48 h.

[0029] The molecular sieve is preferably pretreated with a NaAlO2 solution, and the molar concentration of the NaAlO2 solution, the pretreatment time, and the temperature and time of the second drying are controlled within the above-mentioned ranges, which helps to reduce the silicon-to-aluminum ratio of the molecular sieve and increase its aluminum content. This results in the molecular sieve having more balancing cations after pretreatment, a stronger electrostatic field, and more adsorption centers within its framework. Crushing is preferably performed to help obtain the first molecular sieve of the above-mentioned size.

[0030] In one embodiment of the present application, in the above step S1, a first metal salt solution is used to perform a first metal ion exchange on the first molecular sieve to obtain a second molecular sieve; the ratio of the mass of the first molecular sieve to the volume of the first metal salt solution is 1:5~60kg / L, and / or the temperature of the first metal ion exchange is 40~100°C; and / or, the second molecular sieve is washed, dried and crushed in sequence to obtain a modified molecular sieve, the size of the modified molecular sieve is 100~300 mesh, preferably washed with deionized water, and / or the temperature of the third drying is 60~120°C.

[0031] Using a first metal salt solution to carry out a first metal ion exchange on the first molecular sieve, and controlling the ratio of the mass of the first molecular sieve to the volume of the first metal salt solution within the above range, helps to further improve the surface chemical properties of the first molecular sieve, thereby enhancing the selectivity of the oxygen-containing compound adsorbent for oxygen-containing compounds, and thus helps to more effectively separate oxygen-containing compounds from the Fischer-Tropsch synthetic oil. Preferably, deionized water is used for washing to help remove residual substances in the second molecular sieve. Preferably, the temperature of the third drying is controlled within the above range to help remove moisture attached to the second molecular sieve after washing, thereby ensuring that the molecular sieve has optimal adsorption conditions and structural stability in subsequent steps. Preferably, crushing is used to help obtain a modified molecular sieve of the above size.

[0032] In one embodiment of the present application, in the above step S2, the activated alumina is modified with a second metal using a second metal salt solution and then dried to obtain a binder; the ratio of the mass of the activated alumina to the volume of the second metal salt solution is 1:1~5kg / L, and / or the drying temperature is 100~150℃, and / or the drying time is 10~48h, and / or the size of the binder is 100~300 mesh.

[0033] It is preferred to use a second metal salt solution to carry out second metal modification on the activated alumina and control the ratio of the mass of the activated alumina to the volume of the second metal salt solution, the drying temperature and time within the above range, which helps to increase the adsorption sites, thereby increasing the effective contact area between the adsorbent and the oxygen-containing compound, and further improving the adsorption efficiency of the oxygen-containing compound adsorbent.

[0034] In one embodiment of the present application, the molar concentrations of the first metal salt solution and the second metal salt solution are each independently 0.005 to 0.5 mol / L, and / or the first metal salt solution and the second metal salt solution are each independently selected from any one or more of a metal nitrate solution, a metal carbonate solution and a metal acetate solution.

[0035] It is preferred to control the types and molar concentrations of the first metal salt solution and the second metal salt solution within the above ranges, which helps to further modify the molecular sieve and activated alumina, and helps to evenly distribute the metal elements, thereby improving the selectivity and adsorption efficiency of the oxygen-containing compound adsorbent.

[0036] In one embodiment of the present application, the raw materials also include an auxiliary agent, and / or the mixed mixture is molded using an acid solution to obtain molded particles, the acid solution is a nitric acid solution and / or a citric acid solution, and the size of the molded particles is 1.5 to 3.5 mm; and / or the first drying temperature is 60 to 150°C, and the roasting temperature is 450 to 600°C.

[0037] Preferably, the above-mentioned type of acid solution is used to perform ball-forming on the mixed mixture, which helps the above-mentioned raw materials pass through forming equipment such as a coating machine to form formed particles of the above-mentioned size. At the same time, it improves the microstructure of the oxygen-containing compound adsorbent, such as reducing pore blockage and promoting the formation of pores within the particles, thereby increasing the specific surface area and porosity of the oxygen-containing compound adsorbent, thereby facilitating sufficient contact between the oxygen-containing compound adsorbent and the oxygen-containing compounds in the Fischer-Tropsch synthetic oil, further enhancing the adsorption capacity and selectivity of the oxygen-containing compound adsorbent for oxygen-containing compounds. Preferably, by controlling the temperature of the first drying and the calcination temperature within the above-mentioned range, it is helpful to obtain an oxygen-containing compound adsorbent of the above-mentioned size and having high mechanical strength and stable adsorption performance.

[0038] The beneficial effects of the present application will be further illustrated below with reference to embodiments.

[0039] Example 1

[0040] 1 kg of Y-type molecular sieve was pretreated with 10 L of a 0.05 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-to-aluminum ratio of 2.2. The pretreated molecular sieve was subjected to a second drying at 100° C. for 12 hours and then crushed to 100 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 10 L of a 0.06 mol / L yttrium nitrate solution at 100° C. for a first metal ion exchange at 100° C. for 1 hour to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C., and then crushed to 100 mesh to obtain an active component modified molecular sieve. The mass content of the Y element in the modified molecular sieve was 4.44%.

[0041] 0.5 kg of activated alumina was immersed in 1 L of 0.1 mol / L yttrium nitrate solution for a second metal modification, and then dried at 120° C. for 10 hours and crushed to 100 mesh to obtain a binder metal-modified activated alumina. The mass content of Y in the metal-modified activated alumina was 1.8%.

[0042] 700 g of modified molecular sieve, 300 g of metal-modified activated alumina and 50 g of starch were mixed, and the mixture was formed into 1.5 mm granules by spraying nitric acid solution in a coating machine. The granules were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0043] Example 2

[0044] 1 kg of Y-type molecular sieve was pretreated with 10 L of 0.05 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2.2. The pretreated molecular sieve was subjected to a second drying at 100°C for 12 hours and then crushed to 200 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 25 L of 0.01 mol / L copper nitrate solution at 100°C for a first metal ion exchange at 100°C for 1 hour to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100°C, and then crushed to 200 mesh to obtain a modified molecular sieve. The mass content of Cu element in the modified molecular sieve was 1.6%.

[0045] 0.5 kg of activated alumina was immersed in 1 L of 0.01 mol / L copper nitrate solution for second metal modification, and then dried at 120° C. for 10 hours and crushed to 200 mesh to obtain binder metal-modified activated alumina. The mass content of Cu in the metal-modified activated alumina was 0.13%.

[0046] 700 g of modified molecular sieve, 300 g of metal-modified activated alumina and 50 g of sesbania powder were mixed, and formed into 1.5 mm shaped particles by spraying nitric acid solution in a coating machine. The particles were first dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0047] Example 3

[0048] 1 kg of Y-type molecular sieve was pretreated with 10 L of 0.03 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2.4. The pretreated molecular sieve was subjected to a second drying at 100°C for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 20 L of 0.03 mol / L calcium carbonate solution at 90°C for a first metal ion exchange for 2 hours to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100°C, and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of Ca in the modified molecular sieve was 2.5%.

[0049] 0.5 kg of activated alumina was immersed in 1 L of 0.01 mol / L calcium carbonate solution for a second metal modification, and then dried at 120° C. for 10 hours and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Ca in the metal-modified activated alumina was 0.08%.

[0050] 700 g of modified molecular sieve and 300 g of metal-modified activated alumina were mixed, and the mixture was formed into 1.5 mm shaped particles by spraying nitric acid solution in a coating machine. The particles were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0051] Example 4

[0052] 1 kg of Y-type molecular sieve was pretreated with 10 L of 0.03 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2.4. The pretreated molecular sieve was subjected to a second drying at 100°C for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 20 L of 0.03 mol / L calcium carbonate solution at 90°C for a first metal ion exchange for 2 hours to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100°C, and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of Ca in the modified molecular sieve was 2.5%.

[0053] 0.5 kg of activated alumina was immersed in 1 L of 0.01 mol / L calcium carbonate solution for a second metal modification, and then dried at 120° C. for 10 hours and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Ca in the metal-modified activated alumina was 0.08%.

[0054] 600 g of modified molecular sieve and 400 g of metal-modified activated alumina were mixed, and the mixture was formed into 1.5 mm shaped particles by spraying nitric acid solution in a coating machine. The particles were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0055] Example 5

[0056] 1 kg of X-type molecular sieve was pretreated with 10 L of 0.05 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2. The pretreated molecular sieve was subjected to a second drying at 100°C for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 15 L of 0.03 mol / L copper nitrate solution at 90°C for a first metal ion exchange for 2 hours to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100°C, and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of Cu in the modified molecular sieve was 1.9%.

[0057] 0.5 kg of activated alumina was immersed in 0.5 L of 0.03 mol / L lanthanum nitrate solution for a second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of La in the metal-modified activated alumina was 0.42%.

[0058] 600 g of modified molecular sieve, 400 g of metal-modified activated alumina and 50 g of guar gum were mixed, and the mixture was formed into 1.5 mm shaped particles by spraying nitric acid solution in a coating machine. The particles were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0059] Example 6

[0060] 1 kg of X-type molecular sieve was pretreated with 10 L of 0.03 mol / L NaAlO2 solution for 2 hours to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2.15. The pretreated molecular sieve was subjected to a second drying at 100° C. for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 10 L of 0.04 mol / L barium nitrate solution at 90° C. for a first metal ion exchange for 3 hours to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C. and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of Ba in the modified molecular sieve was 5.5%.

[0061] 0.5 kg of activated alumina was immersed in 2 L of 0.04 mol / L barium nitrate solution for a second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Ba in the metal-modified activated alumina was 2.2%.

[0062] 600 g of modified molecular sieve, 400 g of metal-modified activated alumina and 50 g of guar gum were mixed, and the mixture was formed into 1.5 mm shaped particles by spraying nitric acid solution in a coating machine. The particles were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0063] Example 7

[0064] 1 kg of ZSM molecular sieve was pretreated with 10 L of a 0.1 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-to-aluminum ratio of 30. The pretreated molecular sieve was subjected to a second drying at 120° C. for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 1 kg of the first molecular sieve was added to 40 L of a 0.05 mol / L cobalt nitrate solution at 120° C. for a first metal ion exchange at 120° C. for 1 hour to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C., and then crushed to 300 mesh to obtain a modified molecular sieve having a Co content of 5.9% by mass.

[0065] 1 kg of activated alumina was immersed in 2 L of 0.02 mol / L nickel nitrate solution for a second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Ni in the metal-modified activated alumina was 0.24%.

[0066] 600 g of modified molecular sieve, 400 g of metal-modified activated alumina and 30 g of guar gum were mixed, and formed into 1.5 mm shaped particles by spraying citric acid solution in a coating machine. The particles were then dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0067] Example 8

[0068] 5 kg of 5A molecular sieve was pretreated with 50 L of a 0.04 mol / L NaAlO2 solution for 2 h to obtain a pretreated molecular sieve having a silicon-aluminum ratio of 2.4. The pretreated molecular sieve was subjected to a second drying at 120° C. for 12 h and then crushed to 300 mesh to obtain a first molecular sieve. 5 kg of the first molecular sieve was added to 60 L of a 0.05 mol / L nickel acetate solution at 100° C. for a first metal ion exchange for 1 h to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C. and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of Ni in the modified molecular sieve was 3.5%.

[0069] 3 kg of activated alumina was immersed in 15 L of 0.1 mol / L nickel nitrate solution for second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Ni in the metal-modified activated alumina was 3%.

[0070] 2400 g of modified molecular sieve, 1200 g of metal-modified activated alumina and 120 g of guar gum were mixed, and formed into 2.5 mm shaped particles by spraying citric acid solution in a coating machine. The particles were first dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0071] Example 9

[0072] 1 kg of 5A molecular sieve was pretreated with 10 L of 0.1 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-to-aluminum ratio of 2. The pretreated molecular sieve was subjected to a second drying at 120° C. for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 0.5 kg of the first molecular sieve was added to 4 L of 0.05 mol / L lanthanum nitrate solution at 100° C. for a first metal ion exchange at 100° C. for 1 hour to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C. and then crushed to 300 mesh to obtain a modified molecular sieve having a La content of 5.5% by mass.

[0073] 5 kg of activated alumina was immersed in 8 L of 0.1 mol / L copper nitrate solution for second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Cu in the metal-modified activated alumina was 1%.

[0074] 600 g of modified molecular sieve, 300 g of metal-modified activated alumina and 50 g of guar gum were mixed, and formed into 3.5 mm shaped particles by spraying citric acid solution in a coating machine. The particles were first dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0075] Example 10

[0076] 1 kg of X-type molecular sieve was pretreated with 10 L of 0.1 mol / L NaAlO2 solution for 1 hour to obtain a pretreated molecular sieve having a silicon-to-aluminum ratio of 2. The pretreated molecular sieve was subjected to a second drying at 120° C. for 12 hours and then crushed to 300 mesh to obtain a first molecular sieve. 0.5 kg of the first molecular sieve was added to 4 L of 0.05 mol / L lanthanum nitrate solution at 100° C. for a first metal ion exchange at 100° C. for 1 hour to obtain a second molecular sieve. The second molecular sieve was washed with deionized water, subjected to a third drying at 100° C. and then crushed to 300 mesh to obtain a modified molecular sieve. The mass content of La in the modified molecular sieve was 5.5%.

[0077] 5 kg of activated alumina was immersed in 8 L of 0.1 mol / L copper nitrate solution for second metal modification, and then dried at 120° C. for 10 h and crushed to 300 mesh to obtain binder metal-modified activated alumina. The mass content of Cu in the metal-modified activated alumina was 1%.

[0078] 600 g of modified molecular sieve, 300 g of metal-modified activated alumina and 50 g of guar gum were mixed, and formed into 3.5 mm shaped particles by spraying citric acid solution in a coating machine. The particles were first dried at 100° C. and calcined at 550° C. to obtain an oxygen-containing compound adsorbent.

[0079] Example 11

[0080] The difference from Example 1 is that the total mass of the modified molecular sieve and the metal-modified activated alumina is 1000 g, the mass proportions of the modified molecular sieve and the metal-modified activated alumina are 95% and 5% respectively, and an oxygen-containing compound adsorbent is finally obtained.

[0081] Example 12

[0082] The difference from Example 1 is that the total mass of the modified molecular sieve and the metal-modified activated alumina is 1000 g, the mass proportions of the modified molecular sieve and the metal-modified activated alumina are 40% and 60% respectively, and an oxygen-containing compound adsorbent is finally obtained.

[0083] Example 13

[0084] The difference from Example 1 is that the molar concentration of the NaAlO2 solution is 0.1 mol / L, the silicon-aluminum ratio of the molecular sieve after pretreatment is 2.15, and an oxygen-containing compound adsorbent is finally obtained.

[0085] Example 14

[0086] The difference from Example 1 is that the molar concentration of the NaAlO2 solution is 0.2 mol / L, the silicon-aluminum ratio of the molecular sieve after pretreatment is 1.5, and an oxygen-containing compound adsorbent is finally obtained.

[0087] Example 15

[0088] The difference from Example 1 is that the mass of the first molecular sieve is 1 kg and the volume of the yttrium nitrate solution is 60 L, the mass content of Y in the modified molecular sieve is 10%, and an oxygen-containing compound adsorbent is finally obtained.

[0089] Example 16

[0090] The difference from Example 1 is that the mass of the first molecular sieve is 1 kg and the volume of the yttrium nitrate solution is 70 L, the mass content of Y in the modified molecular sieve is 15%, and an oxygen-containing compound adsorbent is finally obtained.

[0091] Example 17

[0092] The difference from Example 1 is that 1 kg of activated alumina is immersed in 5 L of yttrium nitrate solution to obtain binder metal-modified activated alumina, the mass content of Y in the metal-modified activated alumina is 5%, and finally an oxygen-containing compound adsorbent is obtained.

[0093] Example 18

[0094] The difference from Example 1 is that 1 kg of activated alumina is immersed in 6 L of yttrium nitrate solution to obtain binder metal-modified activated alumina, the mass content of Y in the metal-modified activated alumina is 5.5%, and finally an oxygen-containing compound adsorbent is obtained.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that the active component is Y-type molecular sieve, and an oxygen-containing compound adsorbent is finally obtained.

[0097] Comparative Example 2

[0098] The difference from Example 1 is that the binder is activated alumina, and an oxygen-containing compound adsorbent is finally obtained.

[0099] Test method:

[0100] Separation of C5~C from Fischer-Tropsch oil 12The components are raw materials, and the mass fraction of oxygenates is 0.1-3%. Oxygenates include alcohols, aldehydes, ketones, acids, esters, and ethers. The oxygenate adsorbents obtained in the above examples and comparative examples are loaded into a fixed-bed reactor. The feed is fed at a certain space velocity, and the desorbed product is collected at the outlet of the fixed-bed reactor. The mass content of oxygenates in the desorbed product is measured, and the adsorption capacity is determined as the mass of adsorbed oxygenates (mg) / mass of oxygenate adsorbent (g), with the unit being mg / g. The test results are shown in Table 1.

[0101] Table 1

[0102]

[0103]

[0104] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0105] The present application provides an adsorbent suitable for fixed bed adsorption removal of oxygen-containing compounds in Fischer-Tropsch synthetic oil. The oxygen-containing compound adsorbent uses the modified molecular sieve modified with the first metal of the above type as an active component, which can increase the adsorption center in the modified molecular sieve framework and improve the chemical properties of its surface, thereby further regulating the adsorption performance of the modified molecular sieve. The use of the mesoporous material activated alumina modified with the second metal of the above type as a molding binder can increase the effective contact area between the adsorbent and the oxygen-containing compound, thereby making it easy for the oxygen-containing compound to diffuse in the pores, thereby improving the selectivity and adsorption capacity of the oxygen-containing compound adsorbent for oxygen-containing compounds. In summary, the oxygen-containing compound adsorbent of the present invention has a good adsorption capacity for C4~C 12 The oxygen-containing compounds in Fischer-Tropsch oil (including alcohol compounds, acid compounds, aldehyde compounds, ketone compounds, ester compounds and ether compounds) have high selectivity and high adsorption capacity, which can reduce the content of oxygen-containing compounds in Fischer-Tropsch oil raw materials to below 1 ppm, and at the same time provide raw materials for downstream polyolefin product production processes.

[0106] The above are merely embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. An oxygen-containing compound adsorbent, characterized in that: The oxygen-containing compound adsorbent includes an active component; The active component includes a modified molecular sieve modified by a first metal and a binder attached to the surface of the modified molecular sieve; the binder is a modified activated alumina modified by a second metal; The metal elements involved in the first metal modification and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

2. The oxygen-containing compound adsorbent according to claim 1, characterized in that: The mass content of the first metal element in the modified molecular sieve is 0.05-10%; and / or the mass content of the second metal element in the modified activated alumina is 0.01-5%; and / or, based on the total mass of the modified molecular sieve and the binder being 100%, the mass of the modified molecular sieve accounts for 45 to 95%, preferably 50 to 80%; And / or, the raw powder of the modified molecular sieve is selected from any one or more of FAU type framework structure molecular sieve, LTA type framework structure molecular sieve, MFI type framework structure molecular sieve and CHA type framework structure molecular sieve.

3. The oxygen-containing compound adsorbent according to claim 1 or 2, characterized in that: The transition metal element is selected from any one or more of Ni, Co, Fe, Mn, Cu, Zn, Ag, Cr, Zr and Ti; preferably, the alkaline earth metal is selected from any one or more of Ca, Ba, Sr and Mg; preferably, the rare earth metal is selected from any one or more of Ce, La, Y and Nd.

4. The oxygen-containing compound adsorbent according to any one of claims 1 to 3, characterized in that The oxygen-containing compound adsorbent also includes an auxiliary agent, and the mass content of the auxiliary agent is 1 to 20% based on the total mass of the modified molecular sieve and the binder as 100%, and / or the auxiliary agent is selected from any one or more of methyl cellulose, sesbania powder, guar gum, carboxymethyl cellulose, maltodextrin, starch, polyethylene glycol, glycerol, sodium carboxymethyl cellulose and polyvinyl alcohol.

5. A method for preparing the oxygen-containing compound adsorbent according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, pre-treating and exchanging the molecular sieve with the first metal ion in sequence to obtain a modified molecular sieve; Step S2, subjecting the activated alumina to a second metal modification to obtain a binder; and Step S3, sequentially mixing, molding, first drying and calcining the raw materials including the modified molecular sieve and the binder to obtain the oxygen-containing compound adsorbent; Wherein, the metal elements involved in the first metal ion exchange and the second metal modification are independently selected from any one or more of transition metal elements, alkaline earth metal elements and rare earth metal elements.

6. The preparation method according to claim 5, characterized in that: In the step S1, the molecular sieve is pretreated with a NaAlO2 solution to obtain a pretreated molecular sieve, and the pretreated molecular sieve is sequentially subjected to a second drying and crushing to obtain a first molecular sieve; The molar concentration of the NaAlO2 solution is 0.01-0.1 mol / L, the silicon-aluminum ratio of the pretreated molecular sieve is 2-50, and the size of the first molecular sieve is 100-300 mesh; and / or the pretreatment time is 1-24 h, and / or the second drying temperature is 60-150° C., and / or the second drying time is 12-48 h.

7. The preparation method according to claim 6, characterized in that: In the step S1, the first metal salt solution is used to perform the first metal ion exchange on the first molecular sieve to obtain a second molecular sieve; The ratio of the mass of the first molecular sieve to the volume of the first metal salt solution is 1:5-60 kg / L, and / or the temperature of the first metal ion exchange is 40-100° C.; And / or, the second molecular sieve is washed, dried and crushed in sequence to obtain a modified molecular sieve, the size of the modified molecular sieve is 100-300 mesh, preferably deionized water is used for the washing, and / or the temperature of the third drying is 60-120°C.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In the step S2, the activated alumina is modified with the second metal using a second metal salt solution and then dried to obtain a binder; The ratio of the mass of the activated alumina to the volume of the second metal salt solution is 1:1-5 kg / L, and / or the drying temperature is 100-150°C, and / or the drying time is 10-48 hours, and / or the size of the binder is 100-300 meshes.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The molar concentrations of the first metal salt solution and the second metal salt solution are each independently 0.005 to 0.5 mol / L, and / or the first metal salt solution and the second metal salt solution are each independently selected from any one or more of a metal nitrate solution, a metal carbonate solution and a metal acetate solution.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The raw materials also include an auxiliary agent, and / or the mixed mixture is molded using an acid solution to obtain molded particles, the acid solution is a nitric acid solution and / or a citric acid solution, and the size of the molded particles is 1.5 to 3.5 mm; And / or, the temperature of the first drying is 60-150°C, and the temperature of the calcining is 450-600°C.

Citation Information

Cited By

  • Fluorination pretreatment assisted cobalt-lanthanum bimetal gradient loaded 10X molecular sieve adsorbent and preparation method thereof

    CN121695819A